Impact of coagulation–ultrafiltration on long-term pipe biofilm dynamics in a full-scale chloraminated drinking water distribution system. Issue 11 (21st September 2020) - Pullerits, Kristjan; Chan, Sandy; Ahlinder, Jon; Keucken, Alexander; Rådström, Peter; Paul, Catherine J.
Abstract : Introducing coagulation–ultrafiltration removed bacteria from the drinking water but did not impact nitrification, localizing this process to the biofilm community. Abstract : While pipe biofilms in DWDSs (drinking water distribution systems) are thought to affect the quality of distributed water, studies regarding the microbial processes are impeded by the difficulties in accessing biofilm undisturbed by DWDS maintenance. In this study, pipe sections were removed from a fully operational DWDS for biofilm sampling over two years and three months, and before and after start of ultrafiltration (UF) with coagulation treatment in the drinking water treatment plant (DWTP). Water ( n = 31), surface biofilm (obtained by swabbing, n = 34) and deep pipe biofilm (obtained by scraping, n = 34) were analyzed with 16S rRNA gene amplicon sequencing; with flow cytometry, and chemical and natural organic matter (NOM) analysis as additional parameters for water quality. UF with coagulation decreased the total cell concentration in the DWDS bulk water from 6.0 × 10 5 ± 2.3 × 10 5 cells per ml to 6.0 × 10 3 ± 8.3 × 10 3 cells per ml, including fluctuations due to seasonal change, as well as decreasing most analyzed fractions of NOM. UF treatment of the water revealed that 75% ± 18% of the cells in the water originated from DWDS biofilm, confirmed by SourceTracker analysis, with the rest of the cells likely released from biofilm on DWTP storage tanks. Following UF start, the ASVs (amplicon sequence variants) in the deep pipe biofilm decreased, and Evenness and Shannon diversity indices decreased, reflecting the community's response to the new environment created by the altered water quality. The pipe biofilm community was dominated by ASVs classified as Nitrosomonadaceae, Nitrospira, Hyphomicrobium and Sphingomonas, with relative abundances ranging from 5–78%, and also included ASVs of genus Mycobacterium, genus Legionella and order Legionellales . This community composition, together with the observation that turnover of nitrogen compounds was unchanged by UF start, indicate that nitrification in the DWDS was localized to the pipe biofilm.